Modelling relations between transportation objects using distributed attribute sets - Griškevičius, Rolandas (Transport, 2003)
Relational sets with distributed attributes (RSDA), described in this paper, are used to model relationships between transportation objects. RSDA is a data storage and management model, extending traditional model of E. F. Codd. It has a richer attribute semantics and intersection effect. Because relationships between transportation objects have rich semantics (i.e. relationship between a cargo and a means of transport), special methodology is required to capture relation singularities.First Published Online: 19 Dec 2011